TEACHING CRITICAL THINKING SKILLS (KONFERENSIYA, 2025)
Critical Thinking (CT) has been increasingly recognized as a vital skill forstudents, serving as a key indicator of the quality of their learning. To cultivateeffective critical thinkers, it is essential to integrate CT into the curriculum andteaching methods across all grade levels. This research presents a systematic reviewof existing literature on the instruction of CT skills, culminating in a conceptualframework that outlines four primary debates among researchers in the field. Onesignificant debate centers on whether technology can enhance students' CT skills. Thefindings from current practices suggest that teaching methods often prioritize subjectmatter over the development of CT. This indicates a notable gap in the instruction ofCT skills, particularly regarding innovative teaching strategies and the incorporationof new technologies. Furthermore, the research underscores the necessity foradditional studies aimed at exploring novel approaches to teaching CT skillseffectively. In summary, while there is a growing recognition of the importance ofCT in education, there remains a critical need for more innovative and technologydriven methods to effectively teach these skills in the classroom